2019
DOI: 10.1038/s41433-019-0453-8
|View full text |Cite
|
Sign up to set email alerts
|

The escape of retrobulbar cerebrospinal fluid in the astronaut’s eye: mission impossible?

Abstract: Ophthalmic abnormalities including unilateral and bilateral optic disc edema, optic nerve sheath distention, globe flattening, choroidal folds, and hyperopic shifts have been observed in astronauts during and after long-duration spaceflight. An increased understanding of factors contributing to this syndrome, termed spaceflight-associated neuro-ocular syndrome, is currently a top priority for the ESA and NASA, especially since this medical obstacle could impact the visual health of astronauts as well as the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…We hypothesized that astronauts with less-compliant optic nerve sheaths may be more likely to develop optic disc swelling, given that a greater degree of optic nerve sheath rigidity that prevents further expansion may result in more CSF pressure increase in the subarachnoid space surrounding the optic nerve (2, 3). According to this hypothesis, microgravity-induced ocular changes may be partially determined by the elastic properties of the optic nerve sheath (4). As such, it would be interesting to evaluate the optic nerve sheath response to alterations in CSF pressure as a predictive biomarker for optic disc edema in astronauts (2).…”
mentioning
confidence: 99%
“…We hypothesized that astronauts with less-compliant optic nerve sheaths may be more likely to develop optic disc swelling, given that a greater degree of optic nerve sheath rigidity that prevents further expansion may result in more CSF pressure increase in the subarachnoid space surrounding the optic nerve (2, 3). According to this hypothesis, microgravity-induced ocular changes may be partially determined by the elastic properties of the optic nerve sheath (4). As such, it would be interesting to evaluate the optic nerve sheath response to alterations in CSF pressure as a predictive biomarker for optic disc edema in astronauts (2).…”
mentioning
confidence: 99%
“…The ventricular volume decreased after 7 months post mission but did not return to baseline. Greater lateral ventricular volume increase was also correlated with visual acuity loss Evidence of CSF compartment enlargement related to LDSF and suggests possible role for this in SANS Wostyn 25 et al 2019 Review of select peer-reviewed articles regarding the pathophysiology of SANS ONH edema in astronauts may at least in part result from forcing of perioptic CSF into the ONH along perivascular spaces surrounding the central retinal vessels, related to long-standing microgravity fluid shifts and variations in optic nerve sheath anatomy and compliance. Supports the cephalad fluid shift theory for the pathophysiology of SANS Elwy 26 et al 2020 Review of 19 studies evaluating the role of raised ICP in SANS 8/11 studies found significant increase in ICP after HDT, 3 also showed associated increase in IOP.…”
Section: Resultsmentioning
confidence: 91%
“…They also noted that after 150 days of microgravity exposure, choroidal thickness and TRT increased by 50 μm and 26 μm, respectively. Wostyn et al 25 reviewed multiple papers regarding the cephalad fluid shift and reported that optic nerve head (ONH) edema may at least in part result from the forcing of perioptic CSF into the ONH along perivascular spaces. Gerlach et al 6 reported that on imaging of the optic nerves of healthy volunteers who underwent head down tilt (HDT) for 4.5 hours, fractional anisotropy and axial diffusivity were significantly increased, suggesting increased CSF volume and movement within the optic nerve sheath.…”
Section: Resultsmentioning
confidence: 99%
“…Microgravity is not the only change of circumstance for the cells. Microgravity fluid shift was also believed to exert significant changes in eyes during and after long-duration spaceflight ( Wostyn et al, 2019 ). Therefore, in vivo and long-term studies under stimulated microgravity and in real spaceflight should be carried out.…”
Section: Discussionmentioning
confidence: 99%